Concentration and Purification of Viruses by Adsorption to and Elution from Insoluble Polyelectrolytes - Wallis, Craig (1971)
Acid-resistant, nonenveloped viruses belonging to the enterovirus, reovirus, and adenovirus groups were readily concentrated on PE60, an insoluble cross-linked polyelectrolyte based on isobutylene maleic anhydride. Hydrolysis of PE60 by NaOH increased its capacity to adsorb viruses. Hydrogen ion levels played an important role in virus concentration; optimal pH levels for maximal virus adsorption were between pH 3.0 and 4.5. Undiluted virus was easily concentrated from large volumes on PE60, and the adsorbed virus was readily eluted at pH 8 to 9.